/kwo/ and /y/ in Taiwan Mandarin: Social Factors and Phonetic Variation*. (April 2016) - Tseng, Shu-Chuan
This article studies three phonological variants of /kwo y/ and the acoustic properties of /o/ and /y/ in 1, 159 Taiwan Mandarin face-to-face interviews from social perspectives. Language shift from Southern Min and Hakka towards Taiwan Mandarin, leading to dialect loss, is updated by quantitative evidence derived from a series of sociolinguistic analyses. Social factors including gender, age group, educational level, internet use, and childhood residence significantly correlate with the use of three /kwo y/ variants: the standard form, /w_o/ merger, and /y/ delabialization. The latter two variants are typical Southern Min-accented Mandarin pronunciation. However, results of acoustic analysis of /o/ and /y/ suggest that the influences of Southern Min are significant only in the group with the largest Southern Min exposure. That is, for Taiwan Mandarin in its current form, dialect mixing is progressing due to intensive contact with Southern Min. But it is not a stabilized end form of change, yet.